2D materials as a diagnostic platform for the detection and sensing of the SARS-CoV-2 virus: a bird's-eye view. Issue 23 (20th May 2021) - Ranjan, Pranay; Thomas, Vinoy; Kumar, Prashant
Abstract : This article reviews the use of two-dimensional materials as diagnostic platforms for the detection and sensing of the SARS-CoV-19 virus. Abstract : Worldwide infections and fatalities caused by the SARS-CoV-2 virus and its variants responsible for COVID-19 have significantly impeded the economic growth of many nations. People in many nations have lost their livelihoods, it has severely impacted international relations and, most importantly, health infrastructures across the world have been tormented. This pandemic has already left footprints on human psychology, traits, and priorities and is certainly going to lead towards a new world order in the future. As always, science and technology have come to the rescue of the human race. The prevention of infection by instant and repeated cleaning of surfaces that are most likely to be touched in daily life and sanitization drives using medically prescribed sanitizers and UV irradiation of textiles are the first steps to breaking the chain of transmission. However, the real challenge is to develop and uplift medical infrastructure, such as diagnostic tools capable of prompt diagnosis and instant and economic medical treatment that is available to the masses. Two-dimensional (2D) materials, such as graphene, are atomic sheets that have been in the news for quite some time due to their unprecedented electronic mobilities, high thermal conductivity, appreciable thermal stability, excellent anchoring capabilities, optical transparency, mechanical flexibility, and a unique capability to integrate with arbitrary surfaces. These attributes of 2D materials make them lucrative for use as an active material platform for authentic and prompt (within minutes) disease diagnosis via electrical or optical diagnostic tools or via electrochemical diagnosis. We present the opportunities provided by 2D materials as a platform for SARS-CoV-2 diagnosis.